Determination of sperm sex ratio in bovine semen using multiplex real-time polymerase chain reaction - Trisadee Khamlor (2018)
Gender selection is important in livestock industries; for example, female calves are required in the dairy industry. Sex-sorted semen is commonly used for the production of calves of the desired gender. However, assessment of the sex ratio of the sorted semen is tedious and expensive. In this study, a rapid, cost effective and reliable method for determining the sex ratio was developed using a multiplex real-time polymerase chain reaction (PCR) assay. In this assay, the X and Y chromosome-specific markers, i.e., bovine proteolipid protein (PLP) gene and sex-determining region Y (SRY) were simultaneously quantified in a single tube. The multiplex realtime PCR assay was shown to have high amplification efficiencies (97% to 99%) comparable to the separated-tube simplex real-time PCR assay. The results obtained from both assays were not significantly different (p > 0.05). The multiplex assay was validated using reference DNA of known X ratio (10%, 50%, and 90%) as templates. The measured %X in semen samples were the same within 95% confidence intervals as the expected values, i.e., > 90% in X-sorted semen, < 10% in Y-sorted semen and close to 50% in the unsorted semen. The multiplex real-time PCR assay as shown in this study can thus be used to assess purity of sex-sorted semen. Copyright © 2014 by Asian-Australasian Journal of Animal Sciences.